DETERMINAN KETEPATAN WAKTU PENAGIHAN KLAIM JKN: STUDI KASUS PADA RSUD DR. SOERATNO GEMOLONG - Wahyu Rizky; Airin Muyasaroh; Amara Valentina; Yogi Catur Putra; Septin Maisharah Karyono (LPPM Universitas Awal Bros, 2026)
Claim submission is a crucial aspect of the healthcare financing system, particularly within the context of the National Health Insurance (JKN) program administered by BPJS Kesehatan. A BPJS Kesehatan claim is the process of submitting invoices for healthcare services provided by hospitals to JKN participants, which are then billed collectively to BPJS on a monthly basis. To this end, hospitals are required to submit complete supporting documents that comply with applicable regulations. This study aims to analyze the factors influencing the timeliness of BPJS Health claims submission at Dr. Soeratno Gemolong General Hospital. The method used in this study is a qualitative method with a descriptive approach, which allows the researcher to gain a deep and comprehensive understanding of the issues occurring in the field. Data collection was conducted through triangulation, which combines observation, in-depth interviews with relevant informants, and a document review. The research findings indicate that delays in claim submission are influenced by several factors, including the lack of specific Standard Operating Procedures (SOPs) in the Medical Records unit that detail the claims process, frequent incompleteness of medical records due to important documents not yet being filled out or signed by the attending physician, human resources for claims processing being sufficiently optimized but still facing challenges at certain times due to incomplete medical records, as well as infrastructure constraints such as a lack of computers, scanners, printers, and internet connectivity issues. These factors significantly hinder the document digitization and verification process, resulting in delays in submitting claims to BPJS Kesehatan.